Individual differences in scientists’ aesthetic disposition, aesthetic experiences, and aesthetic sensitivity in scientific work - Jacobi, Christopher; Varga, Peter J.; Jessani, Zohaib; Vaidyanathan, Brandon (Frontiers in Psychology, 2024)
The roles of personality traits in shaping aesthetic experiences in science, such as the frequency of experiencing beauty, awe, and wonder in scientific work, have been almost entirely unexplored. Whereas artists or arts settings such as museums are well studied from a psychological lens, the practice of science has often been seen as purely rational or dry. In response, this study presents novel findings on the critical roles of scientists' personality traits which shape their aesthetic experiences in science.Methods: Based on a very large and representative four-country study of scientists in the fields of biology and physics (N = 3,092), this study analyzed the associations of Big Five personality traits among scientists with i) dispositional aesthetics (DPES-awe), ii) the frequency of aesthetic experiences in scientific work, and iii) aesthetic sensitivity in science. These survey-weighted OLS regression models included extensive statistical controls for sociodemographic factors.As hypothesized, openness is positively, and neuroticism is negatively linked with dispositional aesthetics, the frequency of aesthetic experiences in scientific work, and aesthetic sensitivity in science. Unexpectedly, agreeableness and conscientiousness (but not extraversion) are highly significant and strong predictors of the three trait and state aesthetic experience variables.The aesthetic experience and personality framework of this paper is empirically supported and demonstrates the importance of personality types of scientists in the practice of science. The unexpectedly strong association of agreeableness with aesthetic experiences points to the importance of cooperation, collaboration, and communication to maximize scientific engagement and creativity.